2015
DOI: 10.1038/srep10089
|View full text |Cite
|
Sign up to set email alerts
|

Large enhancement of superconducting transition temperature of SrBi3 induced by Na substitution for Sr

Abstract: The Matthias rule, which is an empirical correlation between the superconducting transition temperature (Tc) and the average number of valence electrons per atom (n) in alloys and intermetallic compounds, has been used in the past as a guiding principle to search for new superconductors with higher Tc. The intermetallic compound SrBi3 (AuCu3 structure) exhibits a Tc of 5.6 K. An ab-initio electronic band structure calculation for SrBi3 predicted that Tc increases on decreasing the Fermi energy, i.e., on decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 11 publications
(12 reference statements)
1
22
0
Order By: Relevance
“…Few people have realized that SOC should influence the superconductivity of those compounds in the past years. Very recently, ABi 3 (A=Sr and Ba) were reinvestigated 18,19 . Haldolaarachchige et al prepared the single crystal sample of BaBi 3 and concluded the physical parameters in detail 18 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Few people have realized that SOC should influence the superconductivity of those compounds in the past years. Very recently, ABi 3 (A=Sr and Ba) were reinvestigated 18,19 . Haldolaarachchige et al prepared the single crystal sample of BaBi 3 and concluded the physical parameters in detail 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Haldolaarachchige et al prepared the single crystal sample of BaBi 3 and concluded the physical parameters in detail 18 . Iyo et al investigated superconductivity in polycrystalline sample of Na doped SrBi 3 19 . However, the role of SOC still has not been discussed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several bismuthalkaline and alkaline-earth metal intermetallic superconductors known, including LiBi [6], NaBi [7], KBi 2 [8], RbBi 2 , CsBi 2 [9], Ca 11 Bi 10-x [10], SrBi 3 [11,12], BaBi 3 [13], and Ba 2 Bi 3 [14]. Recently, intermetallic phases in the Ca-Bi chemical system were examined using theoretical calculations, and three potential superconductors were proposed: CaBi 3 , CaBi, and Ca 3 Bi [15].…”
Section: Introductionmentioning
confidence: 99%